The occurrence of osumilite in pelitic granulites of the Namaqualand metamorphic complex, South Africa - Nowicki, T; Frimmel, H; Waters, D (1995)
The rare mineral osumilite occurs in Mg-rich metapelitic granulites near Bitterfontein in Namaqualand, South Africa. Associated metamorphic rocks contain the assemblage spinel + quartz which has been used to delineate the upper granulite facies zone of the Namaqualand Metamorphic Complex. The osumilite can be described as very Mg-rich, with most of the iron in the state of Fe3+. The presence of osumilite is largely due to a high oxidation state, high Mg/(Mg+Fe2+) ratio, and low H2O activity. Textural evidence exists for three osumilite-forming reactions. Osumilite formation took place at peak metamorphic conditions around 870°C and 5 kbar, and was followed by approximately isoboric cooling resulting in the freezing-in of mineral equilibria at around 760°C. -from Authors